Spiral oblique retinacular ligament reconstruction in correction of swan neck deformity: a case report - Daniati, Sonia; Karna, Made Bramantya; Asmara, A. A. Gde Yuda (International Journal of Research in Medical Sciences, 2024)
Hyperextension of the proximal interphalangeal (PIP) joint and flexion of the distal interphalangeal (DIP) joint constitute swan neck deformity (SND) of the finger. Surgical management is advised if there is extensor lag or functional impairment. We present a case of SND correction using spiral oblique retinacular ligament (SORL) reconstruction. A 34-year old male with SND with a previous history of tendon repair procedure after a cut to the index finger. The index finger got hit by an electric cord six months later and had left his finger untreated, resulting in stiffness and inability to extend the DIP joint. A SORL reconstruction was performed, using flexor carpi radialis tendon. On follow-up examination the patient showed satisfactory outcome with the DIP joint being able to be extended. SORL reconstruction has tenodesis effect, in which it extends the DIP joint as the PIP joint is extended without alteration of extensor mechanism or restriction of joint flexion. SORL reconstruction using tendon graft can be treatment of choice for treating SND.